RELEVANSI DESAIN KURIKULUM TYLER DALAM PEMBELAJARAN PAI DI JENJANG SMP KAJIAN LITERATUR SISTEMATIS TERHADAP IMPLEMENTASI DI ERA KU-RIKULUM MERDEKA - Mohammad Erihadiana; Tiara Khairunnisa; Nayla Luthfia Hasna Salsabila; Mochammad Fikri Haikal (STKIP Subang, 2026)
Islamic Religious Education (PAI) in Junior High Schools (SMP) plays a crucial role in shaping students' faith, morals, and character. However, the implementation of the Independent Curriculum (Kurikulum Merdeka) presents various challenges regarding teachers, students, government support, time allocation, and facilities, necessitating teachers to be creative and adapt teaching methods to student characteristics. This study aims to examine the relevance of Tyler's curriculum model in PAI learning within the context of the Independent Curriculum. This research utilizes a qualitative approach through a Systematic Literature Review (SLR) method. The findings indicate that Tyler's four component objectives, learning experiences, organization, and evaluation remain highly relevant as a rational framework for designing contextual and meaningful PAI learning. Furthermore, identified solutions to the challenges include creative strategies, project-based learning, collaboration with parents, technology utilization, and religious activities. Consequently, by employing this approach, PAI can effectively shape students who are intelligent, religious, and possess noble character.